The meshing and failure analysis of haulage wheels with the effect by shearer's poses. (July 2022) - Ma, De-jian; Wan, Li-rong; Gao, Kui-dong; Zeng, Qing-liang; Wang, Xue-mei
Highlights: A dynamic model of the walking wheel is established affected by shearer's pose. The radial runout is the most violent when the tooth alternating meshing. Shearer's vertical runout causes stress concentration to expand to the pitch line. The shearer's swing around vertical direction causes the axle impact force. With the oblique angle increase, the safety of the tooth surface decreases. Abstract: The high reliability of the longwall shearer is far-reaching to the efficient operation of coal mines and the stable supply of energy. However, traction problems caused by the haulage wheel's failure are prominent. Therefore, for exploring the damage mechanisms of the haulage wheel by the shearer's pose and optimizing the traction structure, a meshing model between haulage wheels and pin row is established, with the non-standard center distance and the oblique angle, respectively. And the effects of the shearer's pose of the jumping and swinging around the vertical direction on meshing performances are studied. The result indicates the radial runout of haulage wheels is the most violent when the teeth alternate meshing, and the maximum runout amplitude is 1.563 mm. With the radial runout increasing, the average peak force increases, and the stress concentration range of the tooth root expands to the pitch line position. The shearer's swing around the vertical direction causes the axial impact force of the haulage wheel. With the swing angle increasing, the stability and safety of the haulage wheel decrease. As the velocity increases, the axial slip on the tooth surface aggravates while effective meshing width decreases when the haulage wheel is affected by oblique angle. The result provides a reference for reducing the shearer's hauling fault.